(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Chronic uterine inversion is an exceptionally rare gynecological condition and may be misdiagnosed due to its nonspecific presentation. It is usually puerperal but may present months to years after delivery, mimicking pelvic masses such as fibroids or cervical polyps. Case Presentation: We report the case of a 30-year-old multiparous woman with a history of home vaginal delivery two years prior, who presented with 8 months of irregular, heavy vaginal bleeding following 14 months of postpartum amenorrhea. On examination, a reddish polypoidal mass was noted protruding through the cervix, initially suspected to be a cervical polyp. Per-operative findings confirmed chronic uterine inversion. Laparotomy with Haultain’s procedure successfully reduced the inversion. Conclusion: Chronic uterine inversion, though rare, should be considered in women with postnatal abnormal uterine bleeding and polypoidal vaginal masses. Early diagnosis and prompt surgical intervention lead to favorable outcomes.